Research and postgraduate supervision during the Coronavirus-19 pandemic: Lessons learned - Chigona, A.; Sosibo, L. (South African Journal of Higher Education, 2024)
The Coronavirus-19 (COVID-19) pandemic imposed new demands for conducting research and postgraduate supervision online. Face-to-face interactions between supervisors and research participants were limited. Consequently, there was heightened attention to the use of information communications technology (ICTs) to mitigate the disruptions. There is not much research on postgraduate supervision during COVID-19. This interpretative-phenomenological qualitative case study analysed innovative strategies that nine purposely selected supervisors reported to have used to manage postgraduate research and supervision during the COVID-19 pandemic. Data were collected through online open-ended questionnaires sent to the supervisors. The constructivist theory underpinned this study. Results showed that while the pandemic was devastating, academic institutions learnt many good lessons regarding leveraging digital technologies for postgraduate students’ supervision. Innovative online supervision pedagogies were invaluable for both supervisors and students. Therefore, during the post COVID-19 era, supervisors must continue leveraging the use of digital technologies in postgraduate supervision to reduce costs and increase master’s and doctoral students’ throughputs and outputs.